Representações sociais de profissionais de vendas: identificando as competências necessárias à formação profissional do vendedor - Rodrigues, Vanusa dos Reis Coêlho (2015)
This work aims to analyze the social representations of the sales professionals, and as a specific goal, to identify the skills that these professionals consider necessary for their vocational training. Given the cultural importance and social depth of this profession, it was in the Theory of Social Representations, that references have been found to try to understand, for example, how values, attitudes, knowledge and information guide the conduct of these professionals. This research involved the preparation of questionnaires for conducting semistructured interviews with eight subjects, from within and outside the state of Sao Paulo, who constituted a group of salesmen whose areas of expertise involved from vendors responsible for obtaining new purchase orders, through vendors working in shops and service vendors. To analyze the collected data we used the ALCESTE software (Analysis of the co-occurring lexemes within the simple statements of a text), a textual data analysis program that aims to discover the information contained in a text. From this analysis it was found that for the professionals interviewed the sales profession brings satisfaction and self-realization. By having a wide role in society and being essential for organizations, it provides high employability; but still it does not receive proper social recognition. For this group, the most successful salesmen are those who speak little, listen more and prioritize satisfaction, as well as the establishment of a trusting relationship with the customer. However, to achieve this and other advantages, it is necessary that the salesmen develop their skills through continuous learning, resulting in the vision of an innovative man/worker, qualified, updated and seeking to learn continuously to meet the demands of this profession that is marginalized by society, a fact with which the professionals have to deal in their practice daily